(untitled) - Rosen, Gary A.; 1957-; Parsons, Karyn; Ironside, Michael; 1950-; 1968-; Gold, Eric L.; Wayans, Damon; (Eric Louis); 1956-; Castle, Nick; Rachmil, Michael; et al. (Universal Home Video, 1998)
When peace breaks out in America, killing machine Major Benson Winifred Payne, United States Marine Corps Special Forces, is given his marching orders--to the unemployment line. Unable to cope with civilian life, Payne is thrust back into the military regimen as commander of the Madison Academy Junior ROTC.
Keywords: United States; Army; Reserve Officers Training Corps; Drama; Employment; Drama; Retired military personnel; Feature films; Comedy films; Video recordings for the hearing impaired